Static water level monitoring of the Devonian Aquifer - Rick Langel; Keith Schilling (Hello World!, 2024)
In 1991, the Iowa Geological Survey (IGS) constructed a three piezometer wellnest at the ISU NE Research Farm. All piezometers are completed in the Devonian’s Cedar Valley Group. NP-1 is completed in the Bassett Member of the Little Cedar Formation (190 feet deep); NP-2 in the Eagle Center Member (130 feet deep); and NP-3in the Hinkle Member (110 feet deep). The Chickasaw Shale Member, a regional confining unit, separates NP-1 from the other wells. In 2022, the IGS began monitoring these piezometers to improve our understanding of spatial and temporal patterns of groundwater hydrology in the Devonian aquifer in North-Central Iowa.